Computer graphics processing technology based on GIS model and its application - Quanpeng Ji (Systems and Soft Computing)
Abstracts: Image processing technology is extensively utilized in various domains of life and production and has been extensively researched. The conventional methods of image processing are incapable of reflecting image data comprehensively whilst ensuring rapid image processing. The study employs a computer graphics processing technique that combines enhanced neural network and geographic information system, aiming to enhance the swiftness and accuracy of extracting picture information. The study categorizes graphic processing into two parts: image acquisition and image information processing. It utilizes an enhanced convolutional neural network algorithm that integrates adaptive algorithms to improve precision and productivity of the image acquisition component. Subsequently, it enhances the throughput and processing speed of the information processing module through a geographic information system. The study findings demonstrate that the GIS-based computer graphics processing technology achieves complete calculation accuracy for one-dimensional images. Moreover, the calculation accuracy for two-dimensional and three-dimensional images is maintained at over 85 %. Adopting the GIS system for graphic processing work can enhance the calculation accuracy of the graphic processing technology. Improving the technology for graphics processing to maintain recognition of over 90 % can guarantee superior image processing capabilities.